Efficacy and safety of tocilizumab in managing cytokine release syndrome after CD19 CAR-T therapy for relapsed or refractory B-cell acute lymphoblastic leukemia - Zhou, Qianyi; An, Yuxin; Zhang, Xiaomei; Xiao, Xia; Bai, Xue; Liu, Pengjiang; Pu, Yedi; Meng, Juanxia; Zhu, Haibo; Lyu, Cuicui; Zhang, Huan; Zhang, Yu; et al. (Frontiers in Immunology, 2025)
PurposeCD19 chimeric antigen receptor T (CAR-T) cell therapy has shown promise in treating relapsed or refractory (R/R) B-cell acute lymphoblastic leukemia (B-ALL), but cytokine release syndrome (CRS) remains a significant side effect.MethodsThis retrospective cohort study investigated the use of tocilizumab for managing CAR-T-related CRS in 45 R/R B-ALL patients.ResultsOf these, 17 patients received tocilizumab, resulting in a significant reduction in the duration of grade 3 CRS compared to those who did not receive the drug. Additionally, 10 patients showed decreased cytokine levels.Importantly, tocilizumab did not impair CAR-T cell expansion or efficacy, nor did it increase the incidence of adverse events.ConclusionThese findings suggest that tocilizumab may be an effective and safe strategy for mitigating CAR-T-related CRS in R/R B-ALL patients, potentially improving patient outcomes and survival.